The First Amendment and State Bans on Teachers' Religious Garb: Analyzing the Historic Origins of Contemporary Legal Challenges in the United States - Walker, Nathan C. (Routledge Research in Religion and Education, 2019)
List of Tables Foreword Acknowledgements Glossaries Preface Chapter I - The Problem and the Plan Chapter II - How Did We Get Here Chapter III - What are the Constitutional Standards? Chapter IV - How Do We Proceed? Chapter V - What are the Establishment Clause Arguments? Chapter VI - What are the Free Exercise Clause Arguments? Chapter VII - Discussion and Decision Chapter VIII - What Have We Learned? Case Abbreviations Index